Thembela Kepe and Lungisile Ntsebeza (eds), Rural Resistance in South Africa: The Mpondo Revolts after Fifty Years: A valuable addition to the history of rural resistance in South Africa (Historia, 2021)
The history of the Mpondoland Revolt has been a subject for debate for some time in the rural resistance history of South Africa. It is therefore fitting that the editors and contributors of this book decided that while many academics and others, interested in the issues of rural resistance history and its direct results were revisiting their consequences, they completed their research by re-evaluating the Mpondoland Revolt, tracing the 50-year period from when it occurred. The Mpondoland Revolt refers to the action taken by the iKongo to reject the tribal and self-government of the Transkei, initiated by the Bantu Authorities Act of 1951. During a protest held in the district of Bizana, community members in the crowd called upon Saul Mabude, a tribal authority to explain the contents and implications of the Act. His failure to do so angered these members to the extent that they ultimately destroyed his house in protest. This sparked what later became known as the Mpondoland Revolt.